2019
DOI: 10.1017/ice.2019.137
|View full text |Cite
|
Sign up to set email alerts
|

Averting a betrayal of trust: System and individual accountability in healthcare infection prevention

Abstract: Television crime plots are formulaic-a body is discovered in an unexpected place, foul play is suspected, evidence is collected, and detectives work to piece together clues. Just as the episode is about to end, the final clue is discovered, revealing the perpetrator. With the criminal caught and jailed, justice ensues and public trust is restored. When a patient is harmed in healthcare, assigning blame is rarely that simple. Each year healthcare-associated infections (HAIs) harm 1 in 31 inpatients; HAIs lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…Srinivisan (2010) has suggested that one of the criteria for an ideal HC system is to provide access to universal HC services with an adequate level of resources and without any financial as well as a social burden. Therefore, the subfactors, namely, "accessibility and accountability to HC services," "developing HC professionals" and "urban-rural divide" should be paid more attention for better health outcomes (Kasthuri, 2018;Bearman and Vokes, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Srinivisan (2010) has suggested that one of the criteria for an ideal HC system is to provide access to universal HC services with an adequate level of resources and without any financial as well as a social burden. Therefore, the subfactors, namely, "accessibility and accountability to HC services," "developing HC professionals" and "urban-rural divide" should be paid more attention for better health outcomes (Kasthuri, 2018;Bearman and Vokes, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare infection prevention programs guide healthcare system responses to evolving infectious diseases threats. 4 Only institutional leaders can provide the necessary resources and institutionalize emergency responses. Keeping leaders engaged is an ongoing challenge.…”
Section: Preparing For the Impromptu Speechmentioning
confidence: 99%
“…Keeping leaders engaged is an ongoing challenge. 4 The emergence of 2019-nCoV is a potent reminder of the ongoing need for consistent funding, prioritization, and relentless simulation of emergency response mechanisms by healthcare systems, even in the face of competing interests. Our ethical mandate is for safe and reliable care, especially in the face of evolving threats; anything less undermines the public's trust.…”
Section: Preparing For the Impromptu Speechmentioning
confidence: 99%
“…6 Without executive sponsorship, no infection prevention program will reach its desired goals. 7 Keeping leaders engaged is an ongoing challenge, calling into question the alignment of health system values. Frustration ensues when the priorities of hospital administrators do not match the course of action advised by the healthcare epidemiologist.…”
Section: Unique Drivers Of Burnout In Healthcare Epidemiologistsmentioning
confidence: 99%